Effect of ionizing radiation on the shear bond strength of two different adhesive systems in primary teeth. in-vitro study - Nourhan Mahmoud Shahin; Basma Mahmoud Nagi; Amin El Sayed Amin; Amira Saad Badran (BMC, 2024)
Abstract Background Radiotherapy is a treatment modality used for head and neck cancer patients. It has a negative influence on bonding strength of adhesives. Little information is available about the effect of radiotherapy on bonding strength of adhesives in primary teeth. Therefore, this in vitro study aimed to detect the best adhesive system and ideal time to apply restorations in primary irradiated teeth regarding adhesive shear bond strength. Methods Dentin samples from primary teeth were randomly assigned to four groups based on restoration application time and radiation exposure, (G1: control, G2: preradiation, G3: 24 h postradiation, and G4: 6 months postradiation) with 20 samples per group. These groups were further divided into 2 subgroups according to the adhesive system used, with 10 samples per subgroup. (1) 3M™ Single Bond Universal Adhesive (SB), (2) 3M AdperSingle Bond 2 (AS). Samples were exposed to gamma radiation from a cobalt-60 machine. One shot of 60 Gy of radiation was delivered. Then samples were subjected to a shear bond strength test. The load was applied until failure and the maximum load was recorded. Numerical data are presented as mean and standard deviation values, then distributed according to Shapiro-Wilk test or Levene's test and analyzed via two-way ANOVA. The significance level was set at p < 0.05 for all tests. Statistical analysis was performed with R statistical analysis software version 4.4.1 for Windows (Team RC, R: A language and environment for statistical computing. R foundation for statistical computing, 2023). Results Compared with the AS subgroup, the SB subgroup presented significantly greater values (p < 0.001). For SB, there was no significant difference among the G1 and G4 groups (p > 0.001). However, there was a significant difference between G1, G2, and G3 (p < 0.001, P = 0.025, P = 0.265 ns respectively), and G3 presented the lowest values. For AS, there was no significant difference between groups G1 and G4 (p =  < 0.001). Compared with the other groups, G3 presented a significant difference (p = 0.265 ns) and the lowest results. Conclusion Restorations performed 24 h after radiation had lower bond strength than those performed six months after radiation. Regardless of the adhesive system used, SB performed better than AS in terms of the shear bond strength.